THE ANALYSIS OF THE MARKET OF PHARMACEUTICALS FOR DYSMENORRHEA TREATMENT - N. Yu. Cherkasova; A. V. Fomina; O. V. Filippova (IRBIS LLC, 2015)
The range and sales analysis of pharmaceuticals for the dysmenorrhea treatment on the market of Russian Federation was carried out. Various groups of medicaments can be used for the dysmenorrhea therapy. Vast majority of medicines is prescribed and can not be used for self-treatment. The most commonly used medicines have quite extensive list of the registered therapeutic indications that complicates the analysis of sales whereas not only patients with dysmenorrhea provide the market requirements. Despite there is a broad assortment, just a few medicines lead in the sales market and have a stabile demand. Federal and local market structures of the dysmenorrhea treatment are slightly different (by the example of the Voronezh region). Pentalgine (in value) and Citramon (in volume) have the greatest sales among analgetics. Among antispasmodic the leader of sales is No-spa.